Сімейне фермерство у реалізації складових концепції сталого розвитку - Яворська, Тетяна Іванівна; Yavorska, Tetiana (Запоріжжя : 2023, 2023)
UA: Обґрунтовано роль господарств населення як основи розвитку сімейного фермерства в Україні. Здійснено оцінку сімейної моделі господарювання у забезпеченні глобальної продовольчої безпеки. Проаналізовано причини, які впливають на відносно низький рівень продуктивності сільського господарства в господарствах населення. Проведено SWOT-аналіз сімейних фермерських господарств в розрізі трьох складових сталого розвитку: економічної, екологічної та соціальної. EN: Тask statement. The purpose of this study is to study the role of family farms in balanced development according to the economic, ecological and social components of the concept of sustainable development. Research results. It was determined that the basis for the creation of family farms in rural areas of Ukraine are households that own plots of land and are engaged in the production and sale of crop and livestock products. The importance of family farms in reducing poverty and improving global food security has been determined. The productivity of agriculture in households and the reasons affecting its relatively low level are analyzed. It is proven that households provide food for their households and produce a variety of products, including fruits, vegetables, meat and dairy products. A SWOT analysis of the functioning of households (potential family farms) in terms of three main components of sustainable development: economic, ecological and social was carried out. Conclusion. It has been proven that family farms are one of the main factors of sustainable development of rural areas. In terms of environmental sustainability, family farms are sustainable if they are diversified and well managed. From a social point of view, family farming is the best way to preserve the countryside, the traditional way of life of the peasants, the formation of a middle class in the countryside and economically strong rural communities. Family farms contribute to the economic sustainability of the agricultural sector, regulate the fulfillment of priority goals of sustainable development and partially ensure the country's food security.
Family farming implementing component concepts of sustainable development
Keywords: сімейне фермерство; господарства населення; домогосподарства; сталий розвиток; економічна складова концепції сталого розвитку; соціальна складова концепції сталого розвитку; family farming; households; sustainable development; economic component of the concept of sustainable development; ecological component of the concept of sustainable development; social component of the concept of sustainable development